(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
Predictions and expectations about more peaceful, safer and cooperative relations in the international system by the beginning of the XXI century, unfortunately, did not come true. Namely, even today we are witnessing numerous violent internal as well as conflicts between states, which solution is not even in sight. Hence, the dilemma about the applicability, efficiency and sustainability of the existing approaches in conflict managing and overcoming inevitably arises, i.e. do they offer an acceptable platform for creating real solutions, as well, what are the main challenges and perspectives regarding such issue. Starting from this point of view, the paper analysis goal is to explore the possible answers to the indicated dilemma. In this regard, the focus is specifically placed on the analysis of the existing challenges and perspectives from the theory-practice relationship, as well as, from the so called exit solutions or outcomes related to the applicability and sustainability of the instruments and methods of conflict settlement and resolution approaches.